Age-Related Hearing Loss: Sensory and Neural Etiology and Their Interdependence - Elliott, Karen L.; Fritzsch, Bernd; Yamoah, Ebenezer N.; Zine, Azel (Frontiers in Aging Neuroscience, 2022)
Age-related hearing loss (ARHL) is a common, increasing problem for older adults, affecting about 1 billion people by 2050. We aim to correlate the different reductions of hearing from cochlear hair cells (HCs), spiral ganglion neurons (SGNs), cochlear nuclei (CN), superior olivary complex (SOC) and the inferior colliculi (IC) with the analysis of various reasons for each one on the sensory deficit profiles. Outer HCs show a progressive loss in an apical-to-basal gradient and inner HCs show a loss in a base-to-apex progression that results in ARHL at high frequencies after 70 years of age. In early neonates, SGNs innervation maintain cochlear HCs, which may depend less on innervation and survival in the mature cochlea. Loss of SNGs results in a considerable decrease ( 50% or more) of cochlear nuclei in neonates, though the loss is milder in older mice and humans. The dorsal cochlear nuclei (fusiform neurons) project directly to the inferior colliculi while most anterior cochlear nuclei reach the SOC. Reducing the number of neurons in the medial nucleus of the trapezoid body affects the interactions with the lateral superior olive to fine-tune ipsi- and contralateral projections that may remain normal in mice and possibly humans. Furthermore, the inferior colliculi receive direct cochlear fibers and second-order fibers from the superior olivary complex, leading to a central hearing reduction in mice and humans. Although ARHL may arise from many complex causes, HC regeneration remains the more significant problem of hearing restoration that would replace the cochlear implant. This review discusses these issues and recent findings in the context of older humans and mice with hearing loss.